Khabarovsk State Institute of Culture as a School for Formation of a Creative Personality - S. N. Skorinov (Moscow Polytechnic University, 2018)
The 50th anniversary of Khabarovsk State Institute of Culture is the date that allows to summarize the results of its activities, to assess the accomplishments and achievements. Over the past years its became one of the leading educational institutions in the Far East Region for the preparation of the policymakers in the sphere of culture, the heads of cultural institutions, the organizers of cultural events and festivals, specialists for libraries, museums, art galleries, Houses of Culture, music and dance teachers. Today Khabarovsk State Institute of Culture realizes the conception of continuing education and offers 91 educational programs corresponding to different levels of education including secondary specialized (2), bachelor degree (29), master's degree (7), specialist (2), postgraduate courses (3), supplementary education for children and adults (8), retraining and advanced training programs (35). The educational process is organized as co-creative work bringing together students and teachers. The cornerstone of the success of education is cooperation and close ties with future employers, local and municipal institutions of culture and arts. The students are involved in creative activities of chairs, museums, theatres, Houses of culture, Philharmonics. Such practice-oriented education enables to prepare qualified, highly competitive graduates required by market. This is demonstrated by the outcomes of the annual employment monitoring held by the RF Ministry of education and science. For four years the Institute maintains highest figures by comparison with the other higher education institutions of culture.